Pengaruh Model PjBL Berbantuan Aplikasi FonBi terhadap Pelafalan Keterampilan Menyaji Teks Laporan Pengamatan Siswa Kelas VIII SMPN 2 Pariaman - Detrial, Claudhea Enjelina; Nursaid, Nursaid; Suryani, Nurul; Rahma, Annisa Nurul; Utami, Vebby Novedra (Journal of Education Language and Innovation, 2023)
This research aims to present the impact of using the project based learning (PjBL) learning model with the help of the FonBi application on the pronunciation of class VIII students at SMPN 2 Pariaman in presenting observation report texts. This research is quantitative and uses an experimental method with a one group pretest-posttest design. Class VIII of SMPN 2 Pariaman was used as the research population using a purposive sampling technique to select one class as a sample. The data collected involves the skill score of presenting observation report text before and after implementing the PjBL learning model with the help of the FonBi application. The instrument used is a performance test, and data analysis involves a normality test and a homogeneity test. The research results show that the value of tcount (15,200) is greater than ttable (1.69913) at a significance level of α 0.05 with a confidence level of 95%. Overall, it can be concluded that the PjBl model with the help of the FonBi application is effective in improving students' pronunciation skills in presenting observation report texts.